2011
DOI: 10.1002/qua.22490
|View full text |Cite
|
Sign up to set email alerts
|

Ergodicity and rapid electron delocalization – The dynamical mechanism of atomic reactivity and covalent bonding

Abstract: Surprisingly, the historical development of the understanding of the concept of covalent bonding is incomplete and the physical mechanism responsible for bonding is still the subject of debate among chemists. We argue that this is primarily due to the key role played by quantum mechanics and the peculiarity of the Coulomb interaction operating between the electrons and nuclei in molecules. A study of the simplest molecules H + 2 and H 2 as well as the π-electron structure of planar conjugated hydrocarbon molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 43 publications
4
27
0
Order By: Relevance
“…While contributing insight, these interpretations of modern quantum chemistry have not provided a convincing and fully accepted resolution of the dispute concerning the nature of covalent bonding. Our own work over a period of 25 years [1][2][3][4][5][6] has pointed to a deeper quantum dynamical origin of covalent bonding. This work has departed significantly from earlier mechanistic interpretations of covalent bonding, but thus far it has had little impact on the earlier and long-held views of the mainstream chemical community.…”
Section: The Current Impassementioning
confidence: 87%
See 2 more Smart Citations
“…While contributing insight, these interpretations of modern quantum chemistry have not provided a convincing and fully accepted resolution of the dispute concerning the nature of covalent bonding. Our own work over a period of 25 years [1][2][3][4][5][6] has pointed to a deeper quantum dynamical origin of covalent bonding. This work has departed significantly from earlier mechanistic interpretations of covalent bonding, but thus far it has had little impact on the earlier and long-held views of the mainstream chemical community.…”
Section: The Current Impassementioning
confidence: 87%
“…Our discussion will employ two very simple but very different theories of electronic structurethe Thomas-Fermi theory and the Hückel model of planar conjugated hydrocarbon molecules -which contain within them a full range of the dominant mechanisms needed to describe covalent bonding. The analysis presented here is in turn based on earlier articles [1][2][3][4][5][6] and a thesis which is not yet published in all its essential parts [7].…”
Section: A Brief History Of Thoughts On Covalent Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…While our own work over a period of 25 years [68,69,72,75,[77][78][79][80][81][82][83], has agreed with Hellmann's [40], Ruedenberg's [49][50][51][52][53][54][55][56][57][58][59], and Feynman's [88] views, it has also expanded on them by exploring the quantum dynamical description of covalent bonding. Noting that Thomas-Fermi (TF) theory [41,42], the original and simplest type of density functional theory (DFT) [45,89], is unable to describe covalent bonding [43][44][45], we analyzed the reasons for this failure in an effort to better understand the basic physics of bonding [68,[78][79][80]. We have found that, at least in simple systems, the source of the problem is the simplified semi-classical form of the TF kinetic energy functional, resulting in a theory that is unable to account for dynamical constraints (non-ergodicity) and slow electron transfer and thus for any hindered internal electron dynamics in atoms and molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Instead it provides a fully consistent alternative interpretation which sheds light on covalent bonding while avoiding, or in a deeper analysis helping to resolve, the apparent contradiction between the theory and the theorem. The next section of this paper will review the salient features of Ruedenberg's [49][50][51][52][53][54][55][56][57][58][59] theory and our contributions to it [68,69,72,75,[77][78][79][80][81][82][83]. We regard it as most useful for those who want to understand covalent bonding in terms of time-independent interpretations of concepts such as electron density, delocalization and energy.…”
Section: Introductionmentioning
confidence: 99%